A Mini Review on Agarwood Tea Development Towards Alternative Utilization of Agarwood Commodity in Indonesia: Mini Review: Agarwood Tea Development - I Gde Adi Suryawan Wangiyana; Supriadi; Aluh Nikmatullah; Sunarpi (Biological Sciences - PJSIR, 2022)
Agarwood leaves were classified into an underutilized commodity by traditional agarwood farmers in Indonesia. These agarwood leaves have become disposal waste from pruning activity carried by agarwood traditional farmers. Several studies have revealed beneficial health effects of agarwood leaves from Aquilaria genus and Gyrinops genus, including antioxidant, antibacterial, anti-hyperglycemic, anti- inflammatory, sedative and laxative activity. Some studies also have reported that agarwood leaves from these genera are a source of herbal drink product called "agarwood tea". The distribution of agarwood species from Aquilaria genus and Gyrinops genus on several islands in Indonesia has been promising to develop this agarwood tea product in Indonesia. Moreover, agarwood leaves utilization into agarwood tea could give Indonesian agarwood farmers additional income during the waiting period of gubal harvesting as the agarwood cultivation's main commodity. Thus, agarwood leaves processing into herbal tea product is valuable alternatives for prospective utilization of agarwood leaves previously underutilized.